Effect of postural education on physical, muscle function, level of pain and quality of life among institutionalize older people with low back pain / Anith Mahirah Ahme - Ahme, Anith Mahirah (Faculty of Health Sciences, 2016)
Low back pain (LBP) was a common problem that most people experience at some point in their lifetime. Generally increased risk of LBP was associated with awkward posture. However, in elderly the incidence of LBP could be due to aging process. Posture education was the one of the treatment choice. However, there was a lack of studies on posture program for LBP among elderly specifically in institutionalize centres. This study was conducted with aimed to determine the effect of postural care on muscle properties, physical function, level of pain and quality of life as well as to determine association between muscle properties with physical performance, level of pain and quality of life. This was experimental study design utilizing pre-test and post-test measurement. The data were collected during baseline and after 8 weeks. Research was conducted in Rumah Seri Kenangan (RSK), Taiping and Cheras. Result shows, there were significant different in muscle strength (upper limb), muscle flexibility (sit and reach), muscle control (TrA and multifidus) with ( p < 0.05) on postural care program. There were association between muscle property and physical function but there were no association between level of pain and quality of life. This study showed that institutionalized elderly with LBP had provide benefits in certain variables .Thus, it is proven that posture education provide some changes among LBP people However, Future studies are needed to explore more on effects of education among elderly with LBP.